Análise da biorremediação de compostos monoaromáticos em água através da pseudomonas aeruginosa - Câmara, Jéssica Maria Damião de Arruda (2016)
The monoaromatic compounds are toxic substances present in petroleum derivades and used broadly in the chemical and petrochemical industries. Those compounds are continuously released into the environment, contaminating the soil and water sources, leading to the possible unfeasibility of those hydrous resources due to their highly carcinogenic and mutagenic potentiality, since even in low concentrations, the BTEX may cause serious health issues. Therefore, it is extremely important to develop and search for new methodologies that assist and enable the treatment of BTEX-contaminated matrix. The bioremediation consists on the utilization of microbial groups capable of degrading hydrocarbons, promoting mineralization, or in other words, the permanent destruction of residues, eliminating the risks of future contaminations. This work investigated the biodegradation kinetics of water-soluble monoaromatic compounds (benzene, toluene and ethylbenzene), based on the evaluation of its consummation by the Pseudomonas aeruginosa bacteria, for concentrations varying from 40 to 200 mg/L. To do so, the performances of Monod kinetic model for microbial growth were evaluated and the material balance equations for a batch operation were discretized and numerically solved by the fourth order Runge-Kutta method. The kinetic parameters obtained using the method of least squares as statistical criteria were coherent when compared to those obtained from the literature. They also showed that, the microorganism has greater affinity for ethylbenzene. That way, it was possible to observe that Monod model can predict the experimental data for the individual biodegradation of the BTEX substrates and it can be applied to the optimization of the biodegradation processes of toxic compounds for different types of bioreactors and for different operational conditions.